Identifying emotional reactions through qualitative audio and text analysis: a comparative approach to methodologies. - Aguado González, Laura; Sañudo, Yeray; Sierra-Pérez, Jorge (Jornada de Jóvenes Investigadores del I3A, 2025)
Oncological services carry a great emotional burden for the patient and knowing the patient's reactions during the service allows improvements to be made. Different forms of analysis help to detect emotions, offering different results and reducing individual biases. Audio analysis is a preferable option to text analysis.